Do fiscal rules undermine public investments? A review of empirical evidence - Sebastian Blesse; Florian Dorn; Max Lay (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2023)
Fiscal rules are a frequent policy measure to restrict deficit-taking among incumbent politicians. In times of increased and sustained investment needs to mitigate the consequences of climate change, and to promote the digital and structural transformation, fiscal rules have become subject to criticism for undermining public investments. We review 20 existing empirical studies examining the impact of numerical fiscal rules on public investments. We also discuss whether more public investments typically come at the cost of higher deficits and whether the effect on public investments differs between rigid and more flexible fiscal rules. Overall, we do not find systematic evidence for a negative effect of fiscal rules on overall public investments. Rigid fiscal rules seem to deter public investments as compared to more flexible and investment-friendly rules which, by contrast, rather increase public investments. Existing evidence does not suggest that public investments systematically come at the cost of higher public deficits (except for more flexible fiscal rules). The design of fiscal rules appears to be crucial for higher public investments.
Keywords: H50; H54; H6; H63; 330; Fiscal rules; public investment; fiscal sustainability; golden rule; literature review